ICT with Open and Distance Learning for Capability Enhancement: Practices of Higher Education Institutions of Nepal - Jha, Anila (Journal of Training and Development, 2020)
This paper deals with the role of Information and Communication Technology (ICT) in higher education institutions in terms of capability enhancement of learners. In addition, the intents of this research paper is to focus towards online and distance education related with higher education institutions of Nepal. Particularly, the relation of ICT with capability enhancement, the relation of ICT and ODL mode of higher education learners, and the relation of ICT and capability with student learning has been explored in this paper. Theoretically, capability enhancement has been discussed in terms of connectivism and learner autonomy. Moreover, the theories of capability enhancement as interpreted by Amartya Sen and Martha Nussbaum have also been used to discuss this issue. Besides contributing to quality human life, ICT is found to be helpful in promoting good behavior and attitudes, increasing their ability toward being, doing, and functioning. Integrating technology in education can help change people’s lives.